Tolerance of turbot Scophthalmus maximus (L.,1758) embryos to the cryoprotectant propane-1,2-diol - Polo, S.; Chereguini-Fernández-Maquieira; María del Olvido; Rasines, Inmaculada; García-de-la-Banda, Inés (1999)
Sí